Design of a square-root architecture: digit-serial approach - BASHAGHA, A. E.; IBRAHIM, M. K. (International journal of electronics, 1994)
A new digit-serial square-root architecture based on radix-2 n arithmetic is presented. First, the conventional binary square-root algorithm is modified to a digit-serial algorithm which is used to design the proposed architecture. This architecture consists of a number of/i-bit controlled add/subtract (CAS) cells. We present two CAS cell architectures. The first is based on the conventional carry feed-back digit serial adder. The second is based on the carry feed-forward adder structure which results in the first reported square-root architecture that can be pipelined down to the bit-level. Furthermore, there is no specification of the type of adder used in the CAS cell. It can be a carry look-ahead or a carry propagate adder. The proposed architecture is general for any digit size and any wordlength.